TAMAN AIR RAMAH ANAK DI KOTA PELAIHARI - Basri, Nurgisdarani; Rahman, Akbar (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
The Child Friendly Water Park in Pelaihari City is designed with Child Friendly Playroom Standards so that children can play safely and comfortably, and learn to recognize water from an early age. The method used in this design is